2012
DOI: 10.1021/ie301605z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reaction Temperature and Catalyst Type on the Formation of Boron Nitride Nanotubes by Chemical Vapor Deposition and Measurement of Their Hydrogen Storage Capacity

Abstract: Boron nitride nanotubes (BNNT) were synthesized over both Fe 3+ impregnated MCM-41 (mobil composition of matter no. 41) and Fe 2 O 3 /MCM-41 complex catalyst systems at relatively low temperatures for 1 h by the chemical vapor deposition technique in large quantities. The formation of BNNT was tailored at different reaction temperatures by changing catalyst type. The use of Fe 3+ -MCM-41 and Fe 2 O 3 as a complex catalyst system led to thin and thick tube formations. The diameters of BNNTs were in the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The most important factor in BNNT synthesis is the proper selection of the catalyst. For this purpose Fe, Al or Mg are widely used in the synthesis of BNNT [3,6]. In this study, four types of catalysts, namely ZnO, Al 2 O 3 , Fe 3 O 4 , and Fe 2 O 3 , were investigated for their performances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important factor in BNNT synthesis is the proper selection of the catalyst. For this purpose Fe, Al or Mg are widely used in the synthesis of BNNT [3,6]. In this study, four types of catalysts, namely ZnO, Al 2 O 3 , Fe 3 O 4 , and Fe 2 O 3 , were investigated for their performances.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they are electrical isolators independent from their size or chirality. In recent studies, it has been indicated that the hydrogen storage capacity of BNNTs is two times greater than that of CNTs [6]. It has been theoretically demonstrated that BNNTs can capture ions selectively creating superhydrophobic surfaces [78].…”
Section: Introductionmentioning
confidence: 99%
“…With the collapsed BN nanotubes, 95 % of the adsorbed H 2 was released above 300 °C, indicating that defective structures would favor chemical interaction. Two other examples of BN nanotubes are given in Table ; the occurrence of chemisorption is confirmed, but at different levels . Unfortunately, these cited works investigated neither the reuse of the BN samples (i.e., after dehydrogenation) nor the evolution of the sample properties (e.g., H 2 uptake and temperatures of desorption) over cycling.…”
Section: Bn Sorbing H2 At 20–25 °Cmentioning
confidence: 99%
“…Twoo ther examples of BN nanotubes are given in Table 1; the occurrence of chemisorption is confirmed, buta td ifferent levels. [34,35] Unfortunately,t hese cited works investigated neither the reuse of the BN samples (i.e.,a fter dehydrogenation) nor the evolution of the sample properties (e.g.,H 2 uptake and temperatures of desorption) over cycling. Another drawback with this system is the complexity involved in developing controlled nanotubes on al arge scale, which increases the cost of storing H 2 per go fm aterial.…”
Section: Bn Nanotubesmentioning
confidence: 99%
“…First predicted in 1994 and synthesized in 1995, boron nitride nanotubes are nanotubes composed of alternating boron and nitrogen atoms . Boron nitride nanotubes are a subject of interest in areas such as structural materials, energy storage, and biomaterials due to their high surface area, strength, and unique electronic structures . In contrast to carbon nanotubes, boron nitride nanotubes have been discovered to be insulators with a band gap of 5.5 eV and have been used as an alternative to carbon nanotubes to help enhance the strength of materials .…”
Section: Introductionmentioning
confidence: 99%